Modelling the interrelationship between factors for adoption of sustainable lean manufacturing: a business case from the Indian automobile industry. Issue 2 (3rd March 2020) - Kumar, Naveen; Mathiyazhagan, K.; Mathivathanan, Deepak
ABSTRACT: Growth of automobile industry plays a significant role in the Indian Economy. Global warming and increased pollution levels force all countries to revisit their environmental policies towards achieving sustainability. In this view, the automobile industry is under tremendous pressure from both customers and government for sustainable development. Therefore, Indian automobile industry focuses on business improvement through profitability enhancement as well as environmental development through sustainable lean manufacturing. Critical success factors (CSFs) for sustainable lean manufacturing are identified from existing literature, and experts' guidance has been considered to carry out the inter-relationship between CSFs in sustainable lean manufacturing implementation using Interpretive Structural Modelling (ISM) methodology. Top management identified as the influential CSFs, which help in implementation of SLM and leading other CSFs. Driving and dependent factors are also summarized in an Indian automobile industry perspective. The result of research based on data collection from small-, medium- and large-scale automobile sectors. It has been analysed earlier that sustainable manufacturing (lean and green practices) delivers superior results. Hence, the automobile industry needs to adopt sustainable lean manufacturing for achieving economy, social and environmental growth. lean manufacturing. Critical success factors (CSFs) for sustainable lean manufacturing are identified from existing literature, and experts' guidance has been considered to carry out the inter-relationship between CSFs in sustainable lean manufacturing implementation using Interpretive Structural Modelling (ISM) methodology. Top management identified as the influential CSFs, which help in implementation of SLM and leading other CSFs. Driving and dependent factors are also summarized in an Indian automobile industry perspective. The result of research based on data collection from small-, medium- and large-scale automobile sectors. It has been analysed earlier that sustainable manufacturing (lean and green practices) delivers superior results. Hence, the automobile industry needs to adopt sustainable lean manufacturing for achieving economy, social and environmental growth.